Bruno Trentin. Lavoro, libertà, conoscenza - Giovanni Mari (Studi e saggi, 2010)
Bruno Trentin. Lavoro, libertà, conoscenza takes into consideration the figure of Bruno Trentin (1926-2007) and his work as a union leader and politician, his numerous writings in the framework of the history of Republican Italy and the transformations induced by the processes of globalisation. From this reflection, conducted from different disciplinary angles and with different political and cultural sensitivity, what emerges clearly is the extremely idiosyncratic significance of Bruno Trentin in both the practice and the theoretical analysis of the labour struggle and the exploration of its problems. A historic contribution featuring a wealth of suggestions, intuitions and reflections, capable of interpreting events and their potential union and political repercussions, within a project for the enhancement of liberty and the social and cultural role of work conducted in an extraordinarily innovative and far-sighted manner.